Pengaruh Risiko Kredit dan Risiko Likuiditas Terhadap Kinerja Keuangan dengan Exchange Rate Sebagai Variabel Moderasi (Kelompok Bank Umum Swasta Nasioanal di Indonesia Periode 2014-2018) - Harevkha, Bunga B1021161136 (Jurnal Manajemen Update, 2020)
The financial performance high of firm value is one purpose of the bank company. The banking financial performance is used as an assessment of the soundness of banks. Therefore, the bank is required to be able to achieve performance, maintain business sustainability and also maintan public confidence. This research is to find out the affect of exchange rateÂ in influencing credit risk and liquidity risk on financial performance. The object in this study is national private commercial bank listed on the OJK (Otoritas Jasa Keuangan) in 2014-2018. Samples and sampling using purposive sampling with 30 sample bank companies . The analytical type useÂ descriptive analysis, verification test, classic assumption test, multiple regression analysis, coefficient of determination analysis and hypothesis testing. Testing with the Eviews version 10 program. The results of the study show that Credit Risk has a negative and significant affect on banking financial performance. Liquidity risk has a positive and significant affect on banking financial performance. Exchange rate is not able to moderate the relationship between credit risk and banking financial performance. Exchange rate is not able to moderate the relationship between liquidity risk and banking financial performance.Â Keywords: Credit Risk, Liquidity Risk, Exchange Rate, and Financial Performance Â Â Â Daftar Pustaka Â Abimayu, Yudha (2016). Analisis Pengaruh BI Rate, Kurs IDR/USD, Produk Domestik Bruto, dan Giro Wajib Minimum Terhadap Loan to Deposit Ratio (Pada Bank Konvensional yang Terdaftar di Bursa Efek Indonesia). Yogyakarta: Fakultas Ekonomi Universitas Negeri Yogyakarta.Annisa, Aulia (2018). Analisis Pengaruh Risiko Perbankan Terhadap Kinerja Keuangan (Pada Perbankan yang terdaftar di BEI). Yogyakarta: Universitas Islam Indonesia..Darmawi, Herman. 2011. Manajemen Perbankan. Bumi Aksara. JakartaDewi, Oktavia Rosana. (2018). Pengaruh Dana Pihak Ketiga, Inflasi, BI Rate dan Kurs Terhadap Profitabilitas Perbankan Syariah Periode 2013-2017. Lampung: Universitas Islam Negeri Raden IntanKansil, Deyby, Sri Murni, and Joy Elly Tulung.